Incentives and peer effects in the workplace: On the impact of envy and wage transparency on organizational design - Jenny Kragl; Benjamin Bental; Peymaneh Safaynikoo (Economic Theory, 2025)
The article is concerned with understanding the impact of social preferences and wage transparency on the optimal organizational design of firms. We consider a moral-hazard environment with envious workers. The integration of workers in one organizational unit yields productive complementarities but also triggers income comparisons and envy. Separating workers rules out social comparison but also precludes productive synergies. Instead, the firm may impose a wage-secrecy policy to keep the latter while avoiding the former. We show that productive synergies and envy are substitutes under unlimited liability when wages are transparent while they become complements when workers earn rents. As a result, firms are much more likely to integrate workers when the latter are protected by limited liability. Furthermore, even when firms can impose wage secrecy, they prefer not to as long as workers are not too envious. In both cases, firms exploit the incentive effect of pay inequality to raise productive efforts and profits. For the same reason, firms may deliberately establish pay inequality by opting for individual performance pay rather than group bonuses. In this sense, transparency and “sunshine laws” may not be in the self-interest of employees, even more so under a positive minimum wage.
Keywords: D63; D82; M52; M54; 330; Other-regarding preferences; Incentives; Organizational design; Integration; Separation; Inequality; Transparency; Wage secrecy; Envy; Team; Synergy